Self-chaotic microlasers for random bit generation - Xiao, Jin-Long; Xiao, Zhi-Xiong; Ma, Chun-Guang; Hao, You-Zeng; Li, Ya-Li; Yang, Yue-De; Huang, Yong-Zhen (Frontiers in Photonics, 2023)
Semiconductor lasers with optical feedback can produce plentiful non-linear dynamics, including periodic and chaotic oscillations, which are usually applied to microwave signals and physical random number generation, respectively. Chaotic semiconductor lasers are especially successful in generating random numbers compared with pseudorandom numbers generated by a computing process. We report a self-chaotic microlaser based on the internal mode interaction of nearly degenerate modes. A special resonator is designed and demonstrated with the two modes’ frequency intervals on the order of GHz. These modes with strong mode beating result in chaos, and physical random bits are obtained from the laser output power at 10 Gb/s. Our proposals provide a novel scheme to generate laser chaos for high-speed random number generation.